THE ROLE OF CRIMINAL LAW IN MAINTAINING PUBLIC ORDER: A STUDY OF HOMELESS PEOPLE AND BEGGARS - Isa, Muhammad Firmansyah; Puluhulawa, Fenty; Imran, Suwitno Yutye (JCH (Jurnal Cendekia Hukum), 2024)
This research discusses the application of criminal sanctions against vagrants and beggars inGorontalo City based on the provisions of Articles 504 and 505 of the Criminal Code and otherrelated regulations. The phenomenon of the increasing number of vagrants and beggars in the cityposes challenges in law enforcement, especially in terms of the effectiveness of the implementationof criminal sanctions and the socio-economic obstacles behind it. This study aims to analyze theimplementation of criminal provisions against homeless people and beggars and identify factorsthat hinder their enforcement. This research uses a qualitative method with an empirical legalapproach, which is obtained through a literature study and interviews with relevant agencies. Theresults show that the application of criminal sanctions has not been running optimally due to weakinter-agency coordination, the absence of specific regional regulations, and cultural factors of thecommunity that still tolerate the practice of begging. Therefore, an integrated legal approach isneeded to create a more just and sustainable repressive, preventive, and rehabilitative solution.